1984
DOI: 10.1038/sc.1984.18
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and haemodynamic responses to tilting and to standing in tetraplegic patients: a review

Abstract: Summary. This paper has reviewed the acute and long-term responses to changes in vertical posture in normal and tetraplegic subjects. It has discussed physiological mechanisms causing orthostatic hypotension in acute cervical spinal cord injured patients, and subsequent factors contributing to its amelioration over time. The long-term adaptive mechanisms are still controversial, probably involving multiple neurological, endocrine, renal, cardiovascular and haemodynamic factors. These factors include inhibition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…1 This may be explained by MAP in AB individuals being`low-normal' during supine rest, whereas some SCI individuals had a resting MAP similar to that normally observed in AB. This latter observation was not related to lesion level or medication, but may be caused by chance, since variation in the SCI population, even if strati®ed for lesion level, is greater than in the ordinary healthy population.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…1 This may be explained by MAP in AB individuals being`low-normal' during supine rest, whereas some SCI individuals had a resting MAP similar to that normally observed in AB. This latter observation was not related to lesion level or medication, but may be caused by chance, since variation in the SCI population, even if strati®ed for lesion level, is greater than in the ordinary healthy population.…”
Section: Discussionmentioning
confidence: 98%
“…1 Unfortunately, spinal cord-injured (SCI) individuals lack muscle pump function and have an impaired sympathetic nervous system causing diculties in the maintenance of cardiovascular homeostasis during orthostatic challenges caused by postural changes.…”
Section: Introductionmentioning
confidence: 99%
“…5 In patients with complete tetraplegia PPH does not occur, probably because the vasoconstrictor buffering is not prevented by de-efferentation of the re flexes originating in the baroreceptors of the aortic arc and carotid sinus.8 This could be explained by some of the mechanisms sug gested as preventing orthostatic hypoten sion in chronic tetraplegics. 17 One possible explanation for the sympto matic PPH in our patient and not in tetra plegics, is an upper thoracic spinal baroref lex that had been interrupted whilst preserv ing the upper sympathetic nerve supply to the cerebral vessels and a part of the heart. Such a purely spinal upper thoracic BP reflex was suggested by Gilliatt et al 18 This hypothesis was supported by Brown and Malliani who showed a spinal reflex homeostatic regulation of BP in cats, with increased sympathetic discharge through the white ramus at the third thoracic level.…”
Section: Discussionmentioning
confidence: 66%
“…The use of elastic binders, corsets, inflatable pressure suits, bladder percussion and sympathomimetic drugs such as epinephrine or ephedorine can only partially control the symptoms associated with OH 11) . Amezinium has already proved to be effective in the therapy of so-called orthostatic dysfunction, which is thought to be a functional disorder without any evidence of autonomic failure [6][7] . Amezinium is a new, indirectly acting sympathomimetic drug which belongs to the noncatecholamines; it acts exclusively on postganglionic sympathetic neurons to cause selective inhibition of intraneuronal monoamine oxidase (MAO) and inhibition of reuptake of noradrenaline, so that it indirectly stimulates not only α-but also β-adrenoreceptors [4][5] .…”
Section: Discussionmentioning
confidence: 99%
“…Amezinium metilsulfate (4-amino-6-methoxy-1-phenyl-piridazinium methyl sulfate, amezinium) is an indirectly acting sympathomimetic drug which belongs to the noncatecholamines [4][5] . While amezinium has been used in the treatment of essential hypotension or orthostatic dysregulation [6][7] , no therapeutic trials on OH in SCI with amezinium have been reported to date. We therefore examined the clinical efficacy of amezinium on OH in cervical cord injuries.…”
Section: Introductionmentioning
confidence: 99%